On constacyclic codes over Z 4 [v]/<v2 -v> and their Gray images - Hai Q. Dinh (2018)
IEEE In this article, we discuss the construction of all constacyclic codes over R = ℤ4[v]=<v2 – v>. Some significant properties of linear codes over R have been explored. The self-dual constacyclic codes for odd length over R are determined. Several examples of (1 + 2v)-constacyclic codes and (3 + 2v)-constacyclic codes over R, whose ℤ4-images are new ℤ4-linear codes with better parameters according to [16], are provided.